Ultraconformable Integrated Wireless Charging Micro-Supercapacitor Skin - Gao, Chang; You, Qing; Huang, Jiancheng; Sun, Jingye; Yao, Xuan; Zhu, Mingqiang; Zhao, Yang; Deng, Tao (Nano-Micro Letters, 2024)
Conformable and wireless charging energy storage devices play important roles in enabling the fast development of wearable, non-contact soft electronics. However, current wireless charging power sources are still restricted by limited flexural angles and fragile connection of components, resulting in the failure expression of performance and constraining their further applications in health monitoring wearables and moveable artificial limbs. Herein, we present an ultracompatible skin-like integrated wireless charging micro-supercapacitor, which building blocks (including electrolyte, electrode and substrate) are all evaporated by liquid precursor. Owing to the infiltration and permeation of the liquid, each part of the integrated device attached firmly with each other, forming a compact and all-in-one configuration. In addition, benefitting from the controllable volume of electrode solution precursor, the electrode thickness is easily regulated varying from 11.7 to 112.5 μm. This prepared thin IWC-MSC skin can fit well with curving human body, and could be wireless charged to store electricity into high capacitive micro-supercapacitors (11.39 F cm−3) of the integrated device. We believe this work will shed light on the construction of skin-attachable electronics and irregular sensing microrobots. Highlights: 1 An ultraconformable skin-like integrated wireless charging micro-supercapacitor (IWC-MSC) could be wireless charged to store electricity into high capacitive micro-supercapacitors (11.39 F cm−3), and fits well with human surface. 2 Building blocks of IWC-MSC skin are all evaporated by liquid precursor, and each part of the device attached firmly benefitting from the liquid permeation, forming a compact and all-in-one configuration. 3 The electrode thickness easily regulated varying from 11.7 to 112.5 μm by controlling the volume of electrode solution precursor.